2011
DOI: 10.3389/fnins.2011.00023
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Via Intestinal Sweet Taste Pathways

Abstract: The detection of nutrients in the gastrointestinal (GI) tract is of fundamental significance to the control of motility, glycemia and energy intake, and yet we barely know the most fundamental aspects of this process. This is in stark contrast to the mechanisms underlying the detection of lingual taste, which have been increasingly well characterized in recent years, and which provide an excellent starting point for characterizing nutrient detection in the intestine. This review focuses on the form and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 184 publications
1
48
0
Order By: Relevance
“…Note that in this context, satiation refers to the processes involved in meal termination whereas satiety refers to the postprandial absence of hunger, which contributes to the determination of the interval between meals. Overall, release of these hormones depends on meal content and is broadly related to energy content but also depends on meal quality (Cummings & Overduin, 2007;Young, 2011). These hormones can act directly on receptors expressed by hypothalamic and/or brain stem neurons and/or indirectly on receptors expressed on vagus nerve terminals that project to the NTS.…”
Section: Humoral Inputsmentioning
confidence: 99%
“…Note that in this context, satiation refers to the processes involved in meal termination whereas satiety refers to the postprandial absence of hunger, which contributes to the determination of the interval between meals. Overall, release of these hormones depends on meal content and is broadly related to energy content but also depends on meal quality (Cummings & Overduin, 2007;Young, 2011). These hormones can act directly on receptors expressed by hypothalamic and/or brain stem neurons and/or indirectly on receptors expressed on vagus nerve terminals that project to the NTS.…”
Section: Humoral Inputsmentioning
confidence: 99%
“…It is been shown by Sutherland et al [26] and Yonug et al [27] that α-gustducin in rodents is expressed in small portion of L-cells (15%), but its density is higher in other enteroendocrine cells (brush cells 57%, 5-HT-containing enterochromaffin cells 27%). It have been shown that L cell exist distinct populations of L cells, and that glucose-sensitive L cells could be located in the upper intestine, with glucose-insensitive L cells located in the lower intestine [1].…”
Section: Discussionmentioning
confidence: 99%
“…Their result indicate that T1R3 may serve as the receptor for sweet perception in mice. Young [27] indicated that intestinal sweet taste molecules was dynamic regulation of expression and that levels of sweet taste molecule transcripts are modulated in the intestine by both luminal and metabolic factors. The present study, sensitive of sweet taste receptor to glucose may also be related to the difference of T1R3 expression level in the intestine from that from tongue although we did not observe this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal glucose is absorbed primarily by two glucose transporters (GTs)-sodium dependent glucose co-transporter 1 (SGLT1) (10,11) and glucose transporter-2 (GLUT2) (12). Data derived from animal experiments indicate that intestinal glucose absorption is modulated, in large part, by intestinal sweet taste receptors (STRs), heterodimers of the G-protein-coupled receptors T1R2 and T1R3 (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Data derived from animal experiments indicate that intestinal glucose absorption is modulated, in large part, by intestinal sweet taste receptors (STRs), heterodimers of the G-protein-coupled receptors T1R2 and T1R3 (11)(12)(13). STRs, in the presence of intestinal sweet tastants, trigger increased expression of SGLT1 and GLUT2 to promote glucose absorption (14,15).…”
Section: Introductionmentioning
confidence: 99%